2020
DOI: 10.1016/j.nucmedbio.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis, in vitro and preliminary in vivo evaluation of the novel glutamine derived PET tracers [18F]fluorophenylglutamine and [18F]fluorobiphenylglutamine

Abstract: Radiosynthesis, in vitro and preliminary in vivo evaluation of the novel glutamine derived PET tracers [ 18 F]fluorophenylglutamine and [ 18 F]fluorobiphenylglutamine.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In another study, two glutamine-derived PET tracers, [ 18 F] 7a ([ 18 F]fluorophenylglutamine) and [ 18 F] 7b ([ 18 F]fluorobiphenylglutamine), were also labeled and evaluated using the same method; however, both tracers had a low affinity toward the rat ASCT-2 transporter in vitro and low uptake in the F98 rat xenograft in vivo ( Figure 9 b). The authors concluded that they would optimize the substituents of the arene ring to obtain a high-quality, glutamine-based PET radiotracer [ 46 ].…”
Section: Ruthenium-catalyzed 18 F-aa Synthesismentioning
confidence: 99%
“…In another study, two glutamine-derived PET tracers, [ 18 F] 7a ([ 18 F]fluorophenylglutamine) and [ 18 F] 7b ([ 18 F]fluorobiphenylglutamine), were also labeled and evaluated using the same method; however, both tracers had a low affinity toward the rat ASCT-2 transporter in vitro and low uptake in the F98 rat xenograft in vivo ( Figure 9 b). The authors concluded that they would optimize the substituents of the arene ring to obtain a high-quality, glutamine-based PET radiotracer [ 46 ].…”
Section: Ruthenium-catalyzed 18 F-aa Synthesismentioning
confidence: 99%

Cancer

Noakes,
Kalamian,
Seyfried
et al. 2023
Ketogenic